2021
DOI: 10.1126/sciadv.abf8630
|View full text |Cite
|
Sign up to set email alerts
|

Control of intestinal inflammation by glycosylation-dependent lectin-driven immunoregulatory circuits

Abstract: Diverse immunoregulatory circuits operate to preserve intestinal homeostasis and prevent inflammation. Galectin-1 (Gal1), a β-galactoside–binding protein, promotes homeostasis by reprogramming innate and adaptive immunity. Here, we identify a glycosylation-dependent “on-off” circuit driven by Gal1 and its glycosylated ligands that controls intestinal immunopathology by targeting activated CD8+ T cells and shaping the cytokine profile. In patients with inflammatory bowel disease (IBD), augmented Gal1 was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 72 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…Accordingly, commensal gut microorganisms were shown to promote the expression of Fut2 gene (that encodes α1,2‐fucosyltransferase 2) in intestinal epithelial cells, increasing the expression of α1,2‐fucose, through the activation of type 3 innate lymphoid cells (ILC3)/IL22 axis, an essential glycogene to assure gut homeostasis [103]. Recently, in colonic biopsies of IBD patients, it was described that upregulation of ST6GAL1 gene, that encodes a α2,6‐sialyltransferase 1, resulted in the inhibition of Galectin (Gal)‐1 binding [104]. This suggests that glycosylation regulates the activity of Gal‐1, a β‐galactoside‐binding protein involved in a variety of biological processes that controls both innate and adaptive cells response, being essential to maintain the gut homeostasis [104].…”
Section: Role Of Glycans In the Breach Of Immune Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, commensal gut microorganisms were shown to promote the expression of Fut2 gene (that encodes α1,2‐fucosyltransferase 2) in intestinal epithelial cells, increasing the expression of α1,2‐fucose, through the activation of type 3 innate lymphoid cells (ILC3)/IL22 axis, an essential glycogene to assure gut homeostasis [103]. Recently, in colonic biopsies of IBD patients, it was described that upregulation of ST6GAL1 gene, that encodes a α2,6‐sialyltransferase 1, resulted in the inhibition of Galectin (Gal)‐1 binding [104]. This suggests that glycosylation regulates the activity of Gal‐1, a β‐galactoside‐binding protein involved in a variety of biological processes that controls both innate and adaptive cells response, being essential to maintain the gut homeostasis [104].…”
Section: Role Of Glycans In the Breach Of Immune Tolerancementioning
confidence: 99%
“…Recently, in colonic biopsies of IBD patients, it was described that upregulation of ST6GAL1 gene, that encodes a a2,6-sialyltransferase 1, resulted in the inhibition of Galectin (Gal)-1 binding [104]. This suggests that glycosylation regulates the activity of Gal-1, a b-galactoside-binding protein involved in a variety of biological processes that controls both innate and adaptive cells response, being essential to maintain the gut homeostasis [104]. Regarding b1,6-GlcNAc branched N-glycans, it has been shown that Mgat5 -/mice exhibit increased susceptibility to develop severe forms of colitis (IBD), as well as experimental autoimmune encephalomyelitis (EAE), an autoimmune disease with clinical similarities to MS [105,106].…”
Section: Altered Self-glycans As Instructors Of Autoreactive Immune R...mentioning
confidence: 99%
“…It has been shown that ST6GAL1 could prevent intestinal inflammation by regulating T cell immunity levels and play a protective effect on IgA nephropathy by inhibiting the production of proinflammatory cytokines in patients. 15,16 While the deficiency of ST6GAL1 could cause exaggerated acute neutrophilic inflammation, increase radiation-induced gastrointestinal damage, and promote the transformation of synovial fibroblasts into a pro-inflammatory phenotype in mice. [17][18][19] For HCC, it has been reported that serum ST6GAL1 levels were positively correlated with tumor FGF19 expression in patients with surgically resected HCC, and could be a novel serum biomarker for lenvatinib-susceptible FGF19-driven HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Further structural, cellular and glycomic studies of these new complexes are needed to demonstrate a universal allosteric mechanism of regulation for Galectins functions. Moreover, taking into account Galectins involvement in many crucial pathologies such as cancer 6,48 and inflammation 49 or infection by pathogens 7 , the discovery of this selectivity switch should also increase the potential to develop molecules modulating Gal-1 interactions and function in specific pathological situations.…”
Section: Discussionmentioning
confidence: 99%